Phase Equilibrium Measurement of Methane Hydrate with Hydrate Promoters - Mohd Jamal, Marlina Iylia (UNIVERSITI TEKNOLOGI PTERONAS, 2012)
In view of the fact that natural gas hydrate is getting more crucial in the oil and gas industry nowadays, either to prevent its formation or to enhance its formation, this project is about the study of three phase equilibria (H-Lw-V) for methane hydrate and performance of hydrate promoters towards methane hydrate formation. Therefore, the purpose of this project is also to analyse two types of hydrate promoters’ ability in escalating methane hydrate formation. All of these phase equilibria measurement of hydrates will be done by using pure water. In this project, main focused will be given towards the study of phase behaviour for methane hydrate with the influence of two hydrate promoters, which are sodium dodecyl sulfate (SDS) and tetrahydrofuran (THF). The phase equilibria for simple methane hydrate was execute as verification data that can be used as a reference to other hydrate phase equilibria which consist of methane and hydrate promoters. By study the phase equilibria of methane hydrate, the result is useful to overcome flow assurance problem in natural gas pipeline. The significant of knowing phase behaviour of methane hydrate with promoters is to be applied for practical applications that desire formation of hydrate such as in natural gas storage and natural gas transportation. The hydrate phase equilibrium will be measured by using Hydreval equipment.